2019
DOI: 10.1155/2019/9414937
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Histogram Specification for Glioma Grading Using Multicenter Data

Abstract: Multicenter sharing is an effective method to increase the data size for glioma research, but the data inconsistency among different institutions hindered the efficiency. This paper proposes a histogram specification with automatic selection of reference frames for magnetic resonance images to alleviate this problem (HSASR). The selection of reference frames is automatically performed by an optimized grid search strategy with coarse and fine search. The search range is firstly narrowed by coarse search of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The accuracy was 98%. By comparing it to the other methods, it was found that its accuracy was higher than that of the histogram [4], Morphology [18], Neuro Fuzzy Classifier [10] and Fuzzy C-means [8], respectively.…”
Section: Performance On the Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy was 98%. By comparing it to the other methods, it was found that its accuracy was higher than that of the histogram [4], Morphology [18], Neuro Fuzzy Classifier [10] and Fuzzy C-means [8], respectively.…”
Section: Performance On the Proposed Methodsmentioning
confidence: 99%
“…Primarily, the brain tumors are medically diagnosed. Thus, the algorithms for the automatic segmentation of the images applied to computerized tomography (CT) scan [1], positron emission tomography (PET) scan [2,3] and magnetic resonance imaging (MRI) [4][5][6][7][8][9][10][11][12] for segmenting the images of the brain tumors from the images of CT, PET and MRI, respectively. There are preprocessing and post processing developments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment 4: We add the comparison method of experiment (3). Radiologist selection and use the classic histogram specification [19], and we also compare the performance of deep learning for glioma grading [38], [39].…”
Section: Experimental Stepsmentioning
confidence: 99%
“…HS can also be used for image standardization. First, the clinician manually selects a set of representative images from the data set and constructs a transfer function based on this set of representative images [19]. All data sets are subjected to histogram matching according to the transfer function, and the images have a highly similar histogram distribution.…”
Section: Introductionmentioning
confidence: 99%